Peranan Alat Musik Dalam Ibadah Gerejawi Abad I-V - Rodenita Br Barus; Antonius Richard Gondowijoyo (Jurnal Teologi dan Pelayanan Kerusso, 2022)
The problem in this paper lies in the use of musical instruments where in the Old Testament musical instruments played a very important role in worship, but in the New Testament the role of musical instruments is not explained and the Greek Orthodox Church does not use musical instruments in worship. This discussion aims to First, the role and use of musical instruments in worship ceremonies during the Old Testament period. Second, to answer the role and use of musical instruments in the ministry of the Lord Jesus and in the early church. The third, to explain why musical instruments are not used in the worship of the Greek Orthodox Church. So this paper uses a historical literature research approach. This paper will describe the role of music in the Old Testament, the role of music in the ministry of the Lord Jesus and in the early church, and the role of music in the Greek Orthodox Church. The conclusion of this paper proves that the role of music has different meanings in the Old Testament, the role of music during the ministry of the Lord Jesus and the early church, and the role of music in the worship of the Greek Orthodox Church. Abstrak Indonesia Permasalahan dalam tulisan ini terletak pada penggunaan alat musik dimana dalam Perjanjian Lama alat musik sangat berperan dalam peribadahan, namun berbeda dalam Perjanjian Baru peran alat musik tidak dijelaskan dan Gereja Orthodox Yunani tidak menggunakan alat musik dalam ibadahnya. Pembahasan ini bertujuan untuk Yang Pertama, peran dan penggunaan alat musik dalam upacara peribadahan pada masa Perjanjian Lama. Yang kedua, untuk menjawab peran dan penggunaan alat musik dalam masa pelayanan Tuhan Yesus dan pada masa gereja mula-mula. Yang ketiga, untuk menjelaskan mengapa alat musik tidak digunakan dalam peribadahan Gereja Orthodox Yunani. Maka tulisan ini menggunakan pendekatan penelitian pustaka bersifat historis. Tulisan ini akan menjabarkan peran musik dalam Perjanjian Lama, peran musik dalam pelayanan Tuhan Yesus dan pada masa gereja mula-mula, dan peran musik dalam Gereja Orthodox Yunani. Kesimpulan dari tulisan ini membuktikan bahwa peran musik memiliki makna yang berlainan baik dalam Perjanjian Lama, peran musik pada masa pelayanan Tuhan Yesus dan gereja mula-mula, dan peran musik dalam ibadah Gereja Orthodox Yunani.